Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 3 £ S. D. Food .......... 1 0 0 Clothing...... 0 8 0 Fuel and Light ...... 0 4 0 Household Sundries ....... 0 1 8 Personal Sundries ........ 0 9 0 £2 3 6 By this standard, 31.1 per cent. of the working class population of York were living below the minimum. (In fact the percentage was larger, since the figure does not take into account those who have sufficient income to live above the minimum standard, but owing to unwise spending live below it.) Of this 31.1 per cent., nearly half, or 14.2 per cent, of the working class population were living in extreme poverty, with an income of less than 33s. 6d. after paying rent, for a man, wife and three children. (2) Inadequate Earnings the Chief Cause of Poverty. The following table shows some of the wage-rates paid before the war and to-day :— AVERAGE WEEKEY EARNINGS. 1938. 1944. Industry. Men. Youths. Women. Girls. Men. Youths. Women. Girls. Iron Stone Quarrying s. d. s. d. s. d. s d. s. d. s. d. s. d. s. d. 60 5 31 0 ... ... 96 0 51 1 ... ... Brick, Pottery, Glass 63 9 26 7 27 10 16 2 106 0 46 1 49 11 30 3 Chemical Paint, Oil 68 8 28 8 32 0 18 1 120 2 43 8 65 3 31 6 Metal Engineering and Shipbuilding 71 11 26 0 32 0 19 8 141 10 50 8 71 8 39 2 Textiles 59 11 24 3 31 1 19 1 97 8 41 9 53 8 35 8 Clothing 64 9 25 2 32 11 17 5 101 2 40 4 50 10 30 10 Food, Drink, Tobacco 67 11 30 3 32 2 19 1 104 0 40 11 53 1 31 7 Paper, Printing, &c 77 1 26 0 33 3 17 10 119 2 34 5 53 4 28 11 Building 67 6 27 4 ... ... 101 6 42 4 60 4 ... Transport 69 4 27 10 35 2 18 5 108 3 46 2 74 2 ... Public Utility Services 66 1 28 4 37 9 20 11 90 5 36 10 48 0 28 1 Government Industrial Establishments 75 2 32 7 44 9 ... 134 6 50 5 84 0 40 4 15X/2/98/13